2023
DOI: 10.3390/ma16072657
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Halide Perovskite Materials ABX3 (B = Pb, X = I, Br, Cl) Assessment of Structural Properties and Band Gap Engineering for Solar Energy

Abstract: The exact control of material properties essential for solar applications has been made possible because of perovskites’ compositional engineering. However, tackling efficiency, stability, and toxicity at the same time is still a difficulty. Mixed lead-free and inorganic perovskites have lately shown promise in addressing these problems, but their composition space is vast, making it challenging to find good candidates even with high-throughput approaches. We investigated two groups of halide perovskite compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In this range, the ionic sizes are suitable for forming a cubic lattice, where the BX 6 octahedra are undistorted, and the A-site cation fits snugly into the cuboctahedral void formed by the twelve X anions. 231,232 Alternatively, tetragonal or hexagonal structures are formed when it exceeds 1. This usually indicates that the A-site cation is too large for the ideal cubic structure, leading to a distortion in the perovskite structure.…”
Section: Challenges In Perovskite Solar Cellsmentioning
confidence: 99%
“…In this range, the ionic sizes are suitable for forming a cubic lattice, where the BX 6 octahedra are undistorted, and the A-site cation fits snugly into the cuboctahedral void formed by the twelve X anions. 231,232 Alternatively, tetragonal or hexagonal structures are formed when it exceeds 1. This usually indicates that the A-site cation is too large for the ideal cubic structure, leading to a distortion in the perovskite structure.…”
Section: Challenges In Perovskite Solar Cellsmentioning
confidence: 99%
“…[38] The structural optimization procedure integral to our calculations relied on Murnaghan's model of state. [39] This optimization aimed to determine the relaxed phase of Pb 2 ScTaO 6 with the minimum energy value, and the resulting lattice parameters are summarized in Table 2. Significantly, a comparison of these optimized parameters with both experimental and theoretical values reveals a remarkable degree of agreement.…”
Section: Structural and Electronic Propertiesmentioning
confidence: 99%
“…However, less theoretical researchers investigated the magnetic properties of 3d TM doped SiC nanotubes. SiC nanotubes have been synthesized by various research groups [30][31][32][33][34][35][36][37][38]. Experimental [39] and theoretical [40][41][42][43][44] research works devoted interactions of TM atoms with SWSiCNTs have reported appreciable changes in the structural, electronic, and magnetic properties of these systems.…”
Section: Introductionmentioning
confidence: 99%